Sulphydryl Levels of Some Human Tissues and Tumours - Doxey, D. (Nature Publishing Group, 1971)
Total, acid-soluble and protein-bound -SH values have been determined in 88 specimens derived from human malignant tumours and non-malignant tissues, together with the corresponding -SH values in tissues from 19 human foetuses obtained at therapeutic abortion. There appears to be a relationship between acid-soluble -SH and protein -SH in carcinomas of the rectum and colon, but not in any other tissues. In the foetuses, -SH values appear to increase with increasing age, to reach a maximum at about mid-term, then level off.